2004
DOI: 10.1002/ccd.20113
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of tungsten coils after peripheral vascular embolization therapy: Influence on outcome and tungsten load

Abstract: The purpose of this study was to evaluate coil corrosion and the long-term outcome after peripheral vascular embolization therapy performed with tungsten coils. We studied 14 patients who received tungsten coils on an average of 26 months prior to follow-up. The protocol included plain radiography and contrast-enhanced magnetic resonance angiography to investigate corrosion of tungsten coils and recanalization of the embolized vessels. Whole blood, hair, and urine tungsten levels were assayed when available. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
(127 reference statements)
0
19
0
Order By: Relevance
“…Bachthaler et al reported W coil corrosion for intracerebral aneurysms and dural fistulae 26 months post-implantation in 9 of 14 patients also by plain radiography, with two patients displaying complete coil resorption. W blood levels were elevated in 6/14 patients and urine levels were elevated in all[60]. Others have reported similar radiographic and blood serum results with the use of W embolisation coils in intracranial aneurysms, abdominal aortic stent grafts, spermatic vein varioceles, oesophageal and gastric varices and other pathological blood vessels(Figure 4 & 5)[61,[67][68][69][70].…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Bachthaler et al reported W coil corrosion for intracerebral aneurysms and dural fistulae 26 months post-implantation in 9 of 14 patients also by plain radiography, with two patients displaying complete coil resorption. W blood levels were elevated in 6/14 patients and urine levels were elevated in all[60]. Others have reported similar radiographic and blood serum results with the use of W embolisation coils in intracranial aneurysms, abdominal aortic stent grafts, spermatic vein varioceles, oesophageal and gastric varices and other pathological blood vessels(Figure 4 & 5)[61,[67][68][69][70].…”
mentioning
confidence: 73%
“…Various causes for this corrosion have been proposed in the literature: Weill et al blame the metallic impurity of the MDS coils [16,63]. This was disproven by studies that spectroscopically verified the purity of the W pre-implantation (>99.9% by mass) [60][61][62]71]. Barrett et al attribute degradation due to mechanical effects of percussive systolic-diastolic blood flow on the spirals [66] but this explanation was nullified when corrosion was observed by radiography in venous fistula drainage pathways with no percussive flow [16] as well as in cannulae of the spermatic vein [66].…”
Section: Corrosion Of Tungsten Coilsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the newgeneration multidetector-row CT , the entire peripheral arterial tree can be examined in a very short acquisition time [21]. It has shown a high diagnostic accuracy in the evaluation of native peripheral arteries, as well as of in- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, a widespread and intensively increasing relevance of transition metals has been observed in a number of industrial, agricultural and medical technologies (Bernot et al, 2006;Hayes, 2008;Ayanda and Adekola, 2011;Rehder, 2016). New technological processes and applications focus on chemical elements that were overlooked in the past only to be recently rediscovered as desirable for the industrial use.…”
Section: Introductionmentioning
confidence: 99%